Assessment of Meteorological Drivers of Surface Radio Refractivity for Terrestrial Communication Planning in Jos, Plateau State - Lami, Usman; Akinbolati, Akinsanmi; Adeyemi, Owolabi; Sule, Abdullahi; Bernard, Sylvanus; Shaibu, Isah; Idris, Adamu (FUDMA Journal of Sciences, 2026)
This study focuses on the Statistical Assessment of Meteorological Drivers of Surface Radio Refractivity for Terrestrial Communication Planning in Jos, Plateau State, Nigeria. Ten years (2011–2020) of satellite-derived meteorological data, including air temperature, atmospheric pressure, relative humidity, and rainfall, were used to compute monthly, seasonal, and annual surface refractivity values. The results show that refractivity is consistently higher during the wet season than the dry season, with mean values of about 275.00 N-units and 200.00 N-units, respectively. Minimum refractivity values ranged from 289.84 to 320.30 N-units, while maximum values varied between 351.53 and 374.01 N-units over the study period. Higher refractivity during the wet season indicates increased signal attenuation due to enhanced atmospheric moisture. Correlation analysis reveals a negative relationship between refractivity and temperature, a mixed response to atmospheric pressure, and positive correlations with relative humidity and rainfall. These findings are significant for radio frequency planning and can aid in optimizing power budgets and improving the reliability of terrestrial radio communication systems [A1] in Jos and similar climatic regions.
Keywords: Refractivity; Terrestrial; Communication; Meteorological; Planning